Key impacts of climate engineering on biodiversity and ecosystems, with priorities for future research. Issue 2 (1st October 2016) - McCormack, Caitlin G.; Born, Wanda; Irvine, Peter J.; Achterberg, Eric P.; Amano, Tatsuya; Ardron, Jeff; Foster, Pru N.; Gattuso, Jean-Pierre; Hawkins, Stephen J.; Hendy, Erica; Kissling, W. Daniel; Lluch-Cota, Salvador E.; et al.
Abstract: Climate change has significant implications for biodiversity and ecosystems. With slow progress towards reducing greenhouse gas emissions, climate engineering (or 'geoengineering') is receiving increasing attention for its potential to limit anthropogenic climate change and its damaging effects. Proposed techniques, such as ocean fertilization for carbon dioxide removal or stratospheric sulfate injections to reduce incoming solar radiation, would significantly alter atmospheric, terrestrial and marine environments, yet potential side-effects of their implementation for ecosystems and biodiversity have received little attention. A literature review was carried out to identify details of the potential ecological effects of climate engineering techniques. A group of biodiversity and environmental change researchers then employed a modified Delphi expert consultation technique to evaluate this evidence and prioritize the effects based on the relative importance of, and scientific understanding about, their biodiversity and ecosystem consequences. The key issues and knowledge gaps are used to shape a discussion of the biodiversity and ecosystem implications of climate engineering, including novel climatic conditions, alterations to marine systems and substantial terrestrial habitat change. This review highlights several current research priorities in which the climate engineering context is crucial to consider, as well as identifying some novel topics for ecological investigation.